Term of Capital, Forms of Capitals and their Conversion - Вадим Валерьевич Радаев (Journal of Economic Sociology, 2010)
The term of “capital” has been greatly used among economic sociologists recently. Many scientists speak about social capital, cultural capital, symbolic capital and other. At the same time the term of “capital” is considered to be self-evident and between forms of capital fairly good confusion exist. Finally in many cases we do not know how to operationalize different forms of capital. It would be a pity in case that these considerations about them do not go out of logic exercises.  This paper gives a solution to this problem.